Evaluate Short-Term Outcomes of Tirofiban in ST-Segment Elevation Myocardial Infarction Patients Undergoing Percutaneous Coronary Intervention: A Meta-Analysis of Randomized Clinical Trials - Quratulain, Muhammad Israr, Huma Naeem Tareen, Asma Hameed, Tufail Ijaz, Muhammad Rehan Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: Patients with ST-phase elevation myocardial infarction (STEMI) present process percutaneous coronary intervention had been analysed in a meta-evaluation to validate the quick-time period effectiveness and protection of tirofiban (PCI). Background: Whether or whether or not tirofiban is beneficial withinside the quick time period for sufferers with STEMI who go through PCI is debatable. Methods: This meta-analysis was carried out by the Cardiology Department BMCH Quetta and Cardiology department Al Qasimi hospital Sharjah, UAE from May, 2023-October, 2023. In a scientific evaluation and meta-evaluation, we in comparison tirofiban use in sufferers with STEMI present process PCI to sufferers now no longer the use of tirofiban. We diagnosed and blended all applicable randomised managed trials via way of means of looking many scientific databases and websites. The relative chance (RR) and 95% CI had been calculated the use of this fixed-results model. Results: There had been a complete of 5008 human beings from 10 randomised managed trials. Death from any purpose (RR 0.79, CI 0.55-1.12, P=0.18), fundamental bleeding (1.37, 0.93-2.03, P=0.11), or the requirement for a transfusion (1.23, 0.94-1.61, P=0.13) had been now no longer affected after 30 days. There had been statistically sizeable variations in minor bleeding (1.29, 1.02-1.63, P=0.04), thrombocytopenia (2.04, 1.40-2.97, P=0.0002), and 6-month all-purpose mortality (0.57, 0.36-0.90, P=0.02). Repeat revascularization (0.58, 0.43-0.78, P=0.0004) and recurrence of myocardial infarction (0.55, 0.33-0.92, P=0.02) had been additionally statistically different. Conclusions: Mild bleeding and thrombocytopenia are much more likely to arise with tirofiban usage, even though the chance of reinfarction, revascularization, and mortality from any purpose after 6 months is lower. Keywords: ST- Segment Elevation, Myocardial Infarction, Tirofiban, Percutaneous Coronary Intervention